The Influence of Paternalistic Leadership Style, Organizational Culture and Working Discipline on Employee Performance PT. Heritage Intan Pratama 2019 - Dadang Baetullah, Dadang Baetullah (Journal of Entrepreneur and Business, 2023)
This research was conducted at PT. Intan Pusaka Pratama, aims: 1)To test and analyze whether there is influence between paternalistic leadership style on employee performance. 2) To test and analyze whether there is influence between organizational culture on employee performance. 3). To test and analyze whether there is influence of work discipline on employee performance. 4) To test and analyze whether there is influence of paternalistic leadership style, organizational culture and work discipline together on employee performance. The type of research used is a quantitative method with data analysis methods by testing two variables, namely the independent variable in the dependent variable, using a questionnaire as a tool for data collection. The samples taken were employees of PT. Intan Pusaka Pratama with a total population of 105 people and a total sample of 51 people. To determine the number of samples with the Slovin formula with an allowance percentage of 10%. From the results of the analysis, paternalistic organizational culture has an effect on employee performance by 7.6%, organizational culture has an effect on employee performance by 22.2, work discipline has an effect on employee performance by 21.1%, while jointly paternalistic leadership style, organizational culture , and work discipline has an effect of s of 28.1%. Keywords: Leadership, Organization, Work Discipline, Performance